2022
DOI: 10.1001/jamaneurol.2022.1457
|View full text |Cite
|
Sign up to set email alerts
|

Time Course for Benefit and Risk With Ticagrelor and Aspirin in Individuals With Acute Ischemic Stroke or Transient Ischemic Attack Who Carry CYP2C19 Loss-of-Function Alleles

Abstract: IMPORTANCEDual antiplatelet therapy (DAPT) with ticagrelor and aspirin has been found to be effective for secondary prevention after minor ischemic stroke or transient ischemic attack (TIA) in individuals who carry CYP2C19 loss-of-function (LOF) alleles; however, uncertainties remain about the time course of benefit and risk with ticagrelor and aspirin in these patients.OBJECTIVE To obtain time-course estimates of efficacy and risk with ticagrelor and aspirin after minor stroke or TIA in individuals with CYP2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The CHANCE-2 trial, a randomized controlled trial among patients with minor IS or TIA who were carriers of CYP2C19 LOF variants, showed patients with CYP2C19 LOF variants may benefit from ticagrelor instead of clopidogrel [18]. The beneficial effect of ticagrelor was predominantly visible in the first week of treatment [19]. However, the study is performed among Chinese patients, and generalizability to non-Asian patients is limited [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHANCE-2 trial, a randomized controlled trial among patients with minor IS or TIA who were carriers of CYP2C19 LOF variants, showed patients with CYP2C19 LOF variants may benefit from ticagrelor instead of clopidogrel [18]. The beneficial effect of ticagrelor was predominantly visible in the first week of treatment [19]. However, the study is performed among Chinese patients, and generalizability to non-Asian patients is limited [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of ticagrelor was predominantly visible in the first week of treatment [19]. However, the study is performed among Chinese patients, and generalizability to non-Asian patients is limited [18, 19]. Further research on Caucasian patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 3 4 An estimate suggests that two thirds of recurrences of stroke within three months occurred within seven days of symptom onset. 5 6 More importantly, the three month high risk period accounts for approximately 70% of subsequent strokes within one year and 40% within five years. 7 8 Exploration of novel treatments are needed to reduce the early recurrent risk of stroke and the overall burden of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In regard of genetics, study on AR is mainly concentrated on single nucleotide polymorphisms (SNPs). SNPs in platelet receptor genes (GP IIIa, 13 GP IV, 14 GP Ibα, 15 PEAR1, 16 P2Y12, and P2Y1 17 ), platelet activation‐related genes (HO‐1, 18 TXB2, 19 COX‐1 and COX‐2 20 ), drug absorption and metabolism genes (CYP2C19, 21,22 ABCB1, 23 UGT1A6 24 ), and lipid metabolism genes (ApoE 25 ) have been proven to be associated with AR. Accordingly, the interactions between gene SNPs is also a factor that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%